The strategy of mind mapping towards teaching reading comprehension of the eleventh grade students - Yunita Dwi Wikandari (PPPM STKIP PGRI Lamongan, 2022)
This research discusses learning Reading Comprehension, which is always referred to as lessons are boring. The objective of this study is to find the strategy of mind mapping in improving students’ reading comprehension achievement, especially for narrative text at the eleventh-grade students of SMA Negeri 1 Mojokerto. The researcher analyzed the data of the post-test by calculating-test. They calculated from the Null hypothesis and alternative hypothesis. The result showed that there is a different mean score between the Experiment group and the Control group. The mean score of the experiment group is 88 and for the control group is 72. The mean score of control group is not better than the experiment group means that the Null hypothesis is rejected. Then, the researcher continued to calculate the alternative hypothesis. The result of the t test is 10,869. After checking the t-table with dk 62 at level 0,05, it was found that the standard of significant is 1,670which means that the result is significant. So, the alternative hypothesis is not rejected. Based on the theoretical hypothesis of this research which is the student learning reading comprehension with Mind Mapping strategy better than the student learning readingcomprehens without Mind Mapping strategy